The extended effect of adsorbed damage-associated molecular patterns and Toll-like receptor 2 signaling on macrophage-material interactions - Kaushal, Anuj; Zhang, Yuxi; Ballantyne, Laurel L.; Fitzpatrick, Lindsay E. (Frontiers in Bioengineering and Biotechnology, 2022)
Implanted biomaterials elicit an immune-mediated foreign body reaction (FBR) that results in the fibrous encapsulation of the implant and can critically impact the performance of some implants. Consequently, understanding the molecular mechanisms that underpin cell-materials interactions that initiate biomaterial-induced inflammation and fibrosis is critical to improving the performance of biomaterial implants negatively impacted by the FBR. Damage associated molecular patterns (DAMPs) are endogenous mediators of inflammation that are released upon tissue injury and induce sterile inflammation via Toll-like receptors (TLRs). However, the prevalence of DAMPs within the adsorbed protein layer on material surfaces and their role mediating cell-material interactions is unclear. Previously, our group demonstrated that molecules in fibroblast lysates adsorbed to various biomaterials and induced a potent TLR2-dependent inflammatory response in macrophages at 24 hours. In this study, we examined the extended response of RAW-Blue reporter macrophages on lysate or serum-adsorbed Teflon™ AF surfaces to understand the potential role of adsorbed DAMPs in macrophage-material interactions at later time points. Lysate-conditioned surfaces maintained increased nuclear factor kappa B (NF-κB) and activator protein 1 (AP-1) transcription factor activity and increased expression Regulated upon Activation, Normal T Cell Expressed and Presumably Secreted (RANTES/CCL5) at 72 and 120 hours, compared to FBS-conditioned surfaces. In contrast, monocyte chemoattractant protein 1 (MCP-1/CCL2) was only elevated at 72 hours in lysate conditions. Transforming growth factor beta 1 (TGF-β1) secretion was significantly increased on lysate-conditioned surfaces, while conditioned media from macrophages on lysate-conditioned surfaces induced alpha smooth muscle actin (αSMA) expression in 3T3 fibroblasts. TLR2 neutralizing antibody treatment significantly decreased NF-κB/AP-1 activity and attenuated TGF-β1 expression at both time points, and MCP-1 and RANTES at 72 hours. Finally, multinucleated cells were observed on lysate-conditioned surfaces at 72 hours, indicating adsorbed DAMPs induced a fusion permissive environment for adherent macrophages. This study demonstrates that adsorbed DAMPs continue to influence macrophage-material responses beyond the initial 24-hour period and maintain a pro-inflammatory and fibrotic response that models aspects of the early FBR. Furthermore, the transient inhibition of TLR2 continued to exert an effect at these later time points, suggesting TLR2 may be a target for therapeutic interventions in FBR.